IMAM ABU HANIFA AND THEORY OF KNOWLEDGE - Raziya Matibaeva (Galaxy International Interdisciplinary Research Journal, 2021)
The article analyzes the work of Imam Abu Hanifa “al-Alim wa-al-mutaallim” (“Teacher and student”), which emphasizes how humbly the student should treat the teacher. Abu Hanifa emphasizes the importance of knowledge for a person that before doing any good deed, he must have enough knowledge about it, and then get down to business. In his work, the scientist effectively used simple examples for easy understanding of the reader.